Turk, Horst / Schultze, Brigitte / Simanowski, Roberto (eds.), Kulturelle Grenzziehungen im Spiegel der Literatur. Nationalismus, Regionalismus, Fundamentalismus. - Gimber, Arno (Revista de Filología Alemana, 1999)
Sin resumen